Persistent C3 vegetation accompanied Plio-Pleistocene hominin evolution in the Malawi Rift (Chiwondo Beds, Malawi). Issue 90 (January 2016) - Lüdecke, Tina; Schrenk, Friedemann; Thiemeyer, Heinrich; Kullmer, Ottmar; Bromage, Timothy G.; Sandrock, Oliver; Fiebig, Jens; Mulch, Andreas
Abstract: The development of East African savannas is crucial for the origin and evolution of early hominins. These ecosystems, however, vary widely in their fraction of woody cover and today range from closed woodland to open grassland savanna. Here, we present the first Plio-Pleistocene long-term carbon isotope (δ 13 C) record from pedogenic carbonate and Suidae teeth in the southern East African Rift (EAR). These δ 13 C data from the Chiwondo and Chitimwe Beds (Karonga Basin, Northern Malawi) represent a southern hemisphere record in the EAR, a key region for reconstructing vegetation patterns in today's Zambezian Savanna, and permit correlation with data on the evolution and migration of early hominins in today's Somali-Masai Endemic Zone. The sediments along the northwestern shore of Lake Malawi contain fossils attributed to Homo rudolfensis and Paranthropus boisei . The associated hominin localities (Uraha, Malema) are situated between the well-known hominin bearing sites of the Somali-Masai Endemic Zone in the Eastern Rift and the Highveld Grassland in southern Africa, and fill an important geographical gap for hominin research. Persistent δ 13 C values around −9‰ from pedogenic carbonate and suid enamel covering the last ∼4.3 Ma indicate a C3 -dominated closed environment with regional patches of C4 -grasslands in the Karonga Basin. The overall fraction of woody cover of 60–70% reflects significantly higher canopy density in the Malawi Rift than the Eastern Rift through time. The discrepancy between the two savanna types originated in the Late Pliocene, when the Somali-Masai ecosystem started to show increasing evidence for open, C4 -dominated landscapes. Based on the Malawi δ 13 C data, the evolution of savanna ecosystems in Eastern Africa followed different patterns along the north-south extent of the EAR. The appearance of C4 -grasses is considered a driver of evolutionary faunal shifts, but despite the difference of ecosystem evolution in the north, similar hominins and suids occurred in both landscapes, pointing to distinct habitat flexibility and also nutritional versatility.